Local Content on the World Wide Web: Maintaining radio as an information channel by the local government - Ahmad Yani; Dian Wardiana Sjuchro (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
The digital transformation has significantly impacted all media sectors, including local government-managed radio. Amid the rapid development of technology and the declining popularity of analog radio, Local Public Broadcasting Institutions (LPPL) are required to innovate to remain relevant and reach broader audiences. This study aims to analyze the media convergence strategies adopted by Radio Kandaga, an LPPL owned by the Bandung Regency Government, to sustain its presence through digital platforms. This research employed a qualitative approach using a case study design conducted over two months (November–December 2024). Data collection techniques included direct observation, in-depth interviews with key informants, and document analysis. The findings indicate that Radio Kandaga implemented convergence strategies through web-based streaming, the use of social media, and the involvement of younger generations as digital content managers. These strategies began with audience behavior observation, followed by adaptive cross-platform programming, and concluded with user engagement-based evaluation. In conclusion, Radio Kandaga has successfully adopted a contextual and adaptive digital strategy that aligns with changing audience media consumption patterns while maintaining its local character as part of its public information service mission and efforts to strengthen transparent local governance.